ANALISIS ETIKA PEJABAT BIROKRASI INDONESIA: Array - Arie Budiawan; Sahadi; Neti Sunarti (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
The method in this research is using the explanatory type, using qualitative analysis techniques, namely by explaining the causal relationship between phenomena with an emphasis on bureaucratic ethics as a determinant of the success of bureaucratic reform in government administration, development and public services. Which is that bureaucratic ethics is essentially closely related to the behavior of the bureaucratic apparatus themselves in carrying out their duties and functions. Efforts to apply good government administration ethics, it is necessary to have rules made to regulate bureaucrats to remain consistent in carrying out and practicing good ethics in government administration. Reinventing Government is a conscious and planned effort to change bureaucratic structures and procedures (reorganizational or institutional aspects); and behavior of bureaucrats (behavioral aspects) in order to increase organizational effectiveness. Designing bureaucratic reform is not just simplifying the bureaucratic structure, but changing the mindset (mind set) and cultural pattern (cultural set) of the bureaucracy to share roles with the role of non-state actors in good governance. Therefore, the reinventing government strategy is implemented in the government bureaucracy through an integral approach that combines structural and cultural approaches. Through the facts, currently there are still many government agencies that have not been able to apply the principles of good administrative ethics, once again this is dependent on the willingness of individuals who work in these agencies to be able to change bad habits and replace them with the application of good administrative ethics